2017
DOI: 10.1016/j.jpor.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of marginal and internal fit of copings fabricated with polyetherketoneketone (PEKK) and zirconia

Abstract: The marginal and internal fit of both PEKK and zirconia copings of both canine and molar were within the clinically acceptable range. However, the PEKK presented better fitness compared with the zirconia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 32 publications
5
47
1
Order By: Relevance
“…Furthermore, both the LC and ZC exhibited positive and negative errors in the inner face generated during the process of combining the digital impressions of the crown. These findings support those of previously published studies on this topic 29303132333435363738394041. The quantitative evaluation of the marginal adaptation is not yet standardized and can be misleading 42.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, both the LC and ZC exhibited positive and negative errors in the inner face generated during the process of combining the digital impressions of the crown. These findings support those of previously published studies on this topic 29303132333435363738394041. The quantitative evaluation of the marginal adaptation is not yet standardized and can be misleading 42.…”
Section: Discussionsupporting
confidence: 84%
“…The abutment tooth of the master model (reference STL, nominal data) and the internal region of the crown (scan data) were alignment-transformed with a 3-D inspection software (Verify, Geomagic GmbH, Stuttgart, Germany) with the obtained STL file. The three-dimensional evaluation method is based on the basic principle of the merging software, which is to mathematically find the best fit for the abutment teeth and dental prostheses at the closest distance 343536. Therefore, accurate merging on one surface can cause errors on other surfaces due to compensation, which does not allow the representation of realistic cement values 343536.…”
Section: Methodsmentioning
confidence: 99%
“…It was also shown that the internal adaptation of a restoration and the retentive force have no significant correlation with each other. Bae 7 reported significantly better internal and marginal fit in polyetherketoneketone (PEKK) copings compared to zirconia, while de Paula Silveira 8 reported better internal adaptation for composite resin compared to a ceramic group. This controversy could be attributed to different types of scanners, milling machines, blanks, or blocks than those used in the present study.…”
Section: P4mentioning
confidence: 99%
“…As fully sintered Y-TZP has high strength, processing takes longer and wears the milling tools more rapidly. 42 As a result, all processing steps are generally conducted with presintered zirconia and sintered after milling. 42 However, sintering results in a linear shrinkage of 20% to 25% and can also affect the fit of a restoration.…”
mentioning
confidence: 99%
“…42 As a result, all processing steps are generally conducted with presintered zirconia and sintered after milling. 42 However, sintering results in a linear shrinkage of 20% to 25% and can also affect the fit of a restoration. 43 Long-span zirconia frameworks have higher marginal gap values, particularly when these are produced from presintered blocks, 17 and the data regarding the marginal and internal discrepancy of CAD-CAM zirconia restorations manufactured using digital scan techniques remain scarce.…”
mentioning
confidence: 99%